Fabrication of dye-sensitized solar cells using anthocyanidins from the extracts of Roselle (Hibiscus sabdariffa). (Fountain Journal of Natural and Applied Sciences, 2016)
This study extracted, purified and applied the extracts of H. sabdariffa as photo-sensitizers in dye-sensitized solar cells. The chemical properties of the extracts were examined using UV, FT-IR and GC-FID spectroscopic studies. The photoelectrochemical properties of the extracts were also reported. U-V spectra showed significant difference in the absorbance and wavelengths of the crude and purified samples of H. sabdariffa (HSE and HSP respectively). The former has characteristic absorptions of 1.096 at 330 nm and 0.211 at 540 nm, and the latter, 0.211 at 335 nm and 0.334 at 540 nm. Shifts in the wavelengths of the absorption (around 330 - 350 nm) and a characteristic decrease in the absorption between the HSE and HSP were observed. The FT-IR spectra of the HSE and HSP have similar characteristic absorbances peculiar to OH, C=O, C-C double bond (both aliphatic and aromatic) and C-O HSP has two additional absorbances at 2365 cm-1 and 2075cm-1. The spectra of the purified sample have bathochromic (red) shifts on the hydroxyl group and hypsochromic (blue) shifts on the benzene. The GC-FID chromatograms revealed the presence of six anthocyanidins and the spectra data showed the amount of the anthocyanidins in mg per 100 g of the sample. The results showed that delphinidin was in abundance, followed by cyanidin in both samples. The quantities of the delphinidin increased with purity of the samples, while the others decreased with purity for both samples. The photovoltaic performances of HSE and HSP have the fill factors of 0.254 and 0.347 and the overall efficiencies of 0.118% and 0.645% respectively. From these data, the purified sample has higher fill factor and efficiency than the unpurified extract.Keywords: Anthocyanins, dye-sensitized, solar cell, extracts, fill factor, efficiency.